HUBUNGAN POWER OTOT LENGAN OVER HEAD PASS BOLA TANGAN PADA MAHASISWAPENDIDIKAN JASMANI KESEHATAN DANREKREASI - Alamsyah; Saifu; Suhartiwi (Journal Olympic (Physical Education, Health and Sport), 2022)
The purpose of this study was to determine the relationship between arm muscle power and the over head pass ability of handball in all 643 students of Physical Education for Health and Recreation. Furthermore, 358 people who had programmed handball courses consisted of 274 boys and 84 girls. The sample was carried out using purposive sampling technique, namely based on predetermined criteria, as many as 30 instruments were used to measure the muscle power of the medicine ball throw arm, while the instrument used to measure the over head pass ability was the 15 second passing skill test. Arm muscle power data was taken through a medicine ball throw test, while data on the over head pass ability were taken through a passing over head pass skill test. The analytical technique used to analyze the proposed hypothesis was the correlation test using SPSS version 26.The results obtained from testing the arm muscle power hypothesis with the ability to over head pass handball where the correlation value rxy = 0.575 significant value = 0.001˂ 0.05, the coefficient of determination r² = 33 or 33%. Arm muscle power contributes to the ability to over head pass in handball play. Based on the results of this analysis, it can be concluded that the better the arm muscle power, the better the ability to over-head pass the handball game for Health and Recreation Physical Education students, Halu Oleo University